ANALISIS KEPUASAN PELAYANAN MUTASI PEGAWAI MENGGUNAKAN METODE FUZZY SERVICE QUALITY (SERVQUAL) - Indrayuni, Elly (Jurnal Pilar Nusa Mandiri, 2017)
Mutation is a change of position the post, a place or employment inside an organization or company that can occur over my own request or request of the company. But there were several problems in the service of mutation employees placement of them is the position of civil servants is in accordance with capacity so that may affect employee motivation work and also the effectiveness of our performance on the company. The purpose of this research is to find satisfaction service employees whether a mutation is according to competence of employees. Methods used in this research is fuzzy service quality (servqual). The results of the analysis method servqual consisting of 52 variables with 5 dimensions that the variable that need undergoing repair namely empathy (emphaty), physical evidence (tangible) and dependability (reliability). The highest the gap shown in dimension sensibility (responsivess) namely 0,034 there is a positive influence and the lowest gap shown in dimension dependability (reliability) namely -0,054 is the negative to the quality of services and satisfaction employees to mutation service employees.